1998
DOI: 10.1046/j.1537-2995.1998.38998409005.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Amicus Separator in the collection of apheresis platelets

Abstract: The Amicus Separator provided satisfactory platelet yields and collection efficiency, with shorter collection times than did the Spectra LRS, and it white cell-reduced components without filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 6 publications
7
24
2
1
Order By: Relevance
“…Compared to results reported in the literature, our COM.TEC CE results (57 ± 15%) were similar to those reported: 52-55% [13,17,18]. However, our Amicus results (55 ± 15%) were lower than the reported averages of 66-73% [8][9][10][11][19][20][21][22]. On the other hand, when comparing the instruments with regard to PLT yield/blood volume processed, the Amicus showed a significantly higher ratio compared to the COM.TEC (0.42 vs. 0.33; p < 0.001).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Compared to results reported in the literature, our COM.TEC CE results (57 ± 15%) were similar to those reported: 52-55% [13,17,18]. However, our Amicus results (55 ± 15%) were lower than the reported averages of 66-73% [8][9][10][11][19][20][21][22]. On the other hand, when comparing the instruments with regard to PLT yield/blood volume processed, the Amicus showed a significantly higher ratio compared to the COM.TEC (0.42 vs. 0.33; p < 0.001).…”
Section: Discussionsupporting
confidence: 85%
“…Using the Amicus, Laurencet et al [20] reported <5 × 10 6 WBC in 98% of the products and <1 × 10 6 WBC in 84%. Additionally, some studies have confirmed the consistency of leukoreduction [9][10][11]21]. In the present study, all products obtained with both instruments had a WBC content <5 × 10 6 (0.30 × 10 6 to 1.2 × 10 6 vs. 0.26 × 10 6 to 1.43 × 10 6 ; p = 0.805).…”
Section: Discussionsupporting
confidence: 76%
“…The present data are in line with those of Stiegler et al, who reported on a median CE of 68% and a PLT yield 4.11 · 10 11 [27]. CE obtained with the discontinuous flow separator MCS+ are similar to those of the Amicus blood cell separator [5][6][7] and higher than those of the AS.TEC 204 and Cobe Spectra devices [2,3,5]. Increased CE may translate into multiple benefits, including increased platelet doses, decreased donor collection time, and/or increased double-unit SDPs harvested.…”
Section: Discussionsupporting
confidence: 93%
“…Once again, Amicus single-needle and Trima Accel were the highest. Others have reported collection efficiencies of 86% for Accel, 67% and 24-116%, for Amicus and 62% for MCS+ [13,15,16].…”
Section: Collection Rates and Efficienciesmentioning
confidence: 98%